[PP.15.31] LIFESTYLE FACTORS EXPLAIN CAROTID-FEMORAL PULSE WAVE VELOCITY IN FINNISH HYPERTENSIVE PATIENTS. (September 2017) - Kantola, I.; Tervo, J.; Koskio, L.; Haijanen, J.; Hermansson, H.; Kantola, T.; Merikari, M.; Makela, P.; Rehunen, S.; Varis, J.
Abstract : Objective: To clarify the explanatory factors of carotid-femoral (C-F) pulse wave velocity (PWV) in Finnish drug-treated hypertensive patients with PWV either <10 m/s or >9.9 m/s. Design and method: A Doppler ultrasonography device (Micro Medical PulseTrace PWV, Micro Medical Ltd, Rochester, Kent, UK) was used to measure C-F PWV in 251 Finnish drug-treated hypertensive patients, The mean age was 60.2 (7.8) years in patients with PWV <10 m/s (61 females and 53 males) and 67.2 (7.2) years in those with PWV >9.9 m/s (65 females and 72 males). 24 hour ambulatory blood pressure monitoring (ABPM) was performed with a portable device (90207 Ambulatory Blood Pressure Monitor, SpaceLabs Inc., Washington, U.S.). Fasting plasma glucose, GHbA1c and lipids and urine albumin/creatinine ratio were measured. SF-36 was calculated. Results: The mean 24 hour systolic blood pressure (SBP) was 124.2 (19.3) and diastolic blood pressure (DBP) 74.2 (12.0) mmHg in patients with PWV <10 m/s and 133.7 (12.2) and 76.5 (6.6) mmHg in those with PWV >9.9 m/s. The mean C-F PWV was 8.3 (1.3) m/s in patients with PWV <10 m/s and 12.8 (3.5) m/s in those with PWV >9.9 m/s. The age of the patients was 59.7 (9.1) years in patients with PWV <10 m/s and 67.2 (7.2) years in those with PWV >9.9 m/s. According to stepwise linear regression analysis C-F PWV was explained by the amount of alcohol used/week (t = -4.718, p = 0.001), GHbA1c (t = 2.988, p = 0.005) and SD of the daytime systolic blood pressure (t = -2.231, p = 0.032) in patients with PWV <10 m/s and by serum creatinine (t = 1.732, p = 0.086), age (t = 3.227, p = 0.02) and weight (t = 2.360, p = 0.02) in those with PWV >9.9 m/s. Conclusions: Among patients with PWV <10 m/s, higher PWV values were explained by more abundant use of alcohol, worse diabetic control and lower daytime SBP variation. Among patients with PWV >9.9 m/s, higher PWV values were explained by higher age and weight and worse renal function.